Measurement of Overconfidence, Illusion of Control and Optimism in the Context of Behavioral Finance: Case of University Students - Tekin, Bilgehan (Muş Alparslan Üniversitesi, 2020)
Davranışsal finans, piyasa anomalilerinin yanı sıra bu anımalilere neden olan önyargıların incelenmesini de konu almaktadır. Literatüre bakıldığında kişilerin karar süreçleri üzerinde etkisi olduğu belirtilen çok sayıda önyargıdan bahsedildiği görülmektedir. Bunlar arasında üzerinde ayrıca durulan önyargıların ise kendine aşırı güven, kontrol yanılsaması ve aşırı iyimserlik olduğu dikkati çekmektedir. Bu çalışmada bu üç önyargının ölçülmesini hedefleyen ifadelerden oluşan ölçeklerin Türkiye’de üniversite öğrencileri üzerindeki güvenilirliği ve geçerliliği test edilmiştir. Önyargıları ölçülmesini hedefleyen ve bu çalışmada kullanılan ölçeğin ilk halinde 19 madde yer almaktadır. Öğrencilerin demografik bilgilerini de içeren anket formu farklı üniversitelerde öğrenim gören toplam 522 öğrenciye uygulanmıştır. Yapılan analizler sonucunda ölçeğin son halinin Cronbach Alfa değerinin 0, 825 olduğu ve ölçekte yer alan ifadelerin 4 faktör altında toplandığı tespit edilmiştir.

Behavioral finance is concerned with analyzing market anomalies as well as biases that cause these anomalies. There are many biases that are stated to have an effect on the decision processes of individuals in behavioural finance literature. It is noteworthy that the biases emphasized among them are overconfidence, illusion of control and extreme optimism. This study aimed at measuring the scale that consists of statements about these three biases on college students in Turkey and reliability and validity of this scale was tested. There are 19 items in the first version of the scale that aims to measure biases and used in this study. The questionnaire, including the demographic information of the students, was applied to a total of 522 students studying at different universities. As a result of the analyzes, it was determined that the final version of the scale Cronbach's Alpha value is 0.825 and the items in the scale were collected under 4 factors.
Davranışsal Finans Bağlamında Kendine Aşırı Güven, Kontrol Yanılsaması ve İyimserlik Önyargılarının Ölçülmesi: Üniversite Öğrencileri Örneği
anemon
Keywords: Davranışsal Önyargılar; Kendine Aşırı Güven; Kontrol Yanılsaması; İyimserlik; Ölçme; Behavioral biases; Overconfidence; The İllusion of Control; Optimism; Measurement